2016
DOI: 10.1371/journal.pone.0157526
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Motor Circuits after Piano Training in Adulthood: Neurophysiologic Evidence

Abstract: The neuronal mechanisms involved in brain plasticity after skilled motor learning are not completely understood. We aimed to study the short-term effects of keyboard training in music-naive subjects on the motor/premotor cortex activity and interhemispheric interactions, using electroencephalography and transcranial magnetic stimulation (TMS). Twelve subjects (experimental group) underwent, before and after a two week-piano training: (1) hand-motor function tests: Jamar, grip and nine-hole peg tests; (2) elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In MI tasks with object-related movement, the vividness of MI is parametrically associated with neural activity within sensorimotor areas (Lorey et al, 2011 ). In MI tasks with finger tapping, MI quality assessment by VAS correlated with the activity of the right orbitofrontal cortex (Houdayer et al, 2016 ). These results support our findings and it is suggested that brain activity during MI could change depending on MI quality assessment, which is the degree of vividness in the task of MI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In MI tasks with object-related movement, the vividness of MI is parametrically associated with neural activity within sensorimotor areas (Lorey et al, 2011 ). In MI tasks with finger tapping, MI quality assessment by VAS correlated with the activity of the right orbitofrontal cortex (Houdayer et al, 2016 ). These results support our findings and it is suggested that brain activity during MI could change depending on MI quality assessment, which is the degree of vividness in the task of MI.…”
Section: Discussionmentioning
confidence: 99%
“…The MI task included playing the piano with both hands. The music used in the task was partially modified concerning the piano task used in a previous study (Houdayer et al, 2016 ), considering the difficulty of playing the piano with both hands. Subjects played the piano with a music score shown in Figure 1 ( Figure 2 shows musical notes on a piano keyboard).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a single session of motor training, it has been found that the power decreases during and after the training (Andres et al, 1999 ; Serrien and Brown, 2003 ; Domingues et al, 2008 ; Nakano et al, 2013 ; Kiefer et al, 2014 ); however, the opposite has also been reported (Etnier et al, 1996 ). For studies where a task is trained over several weeks, the power has been shown to both decrease (Kaiser et al, 2014 ; Borghini et al, 2016a ) and increase (Kerick et al, 2004 ; Borghini et al, 2016b ; Houdayer et al, 2016 ). The affected EEG rhythms include theta, mu/alpha and beta, but again the reported frequency bands in which changes occur are not consistent across studies.…”
Section: Introductionmentioning
confidence: 99%
“…In an MRI study, pianists were characterized by symmetrical size of the primary motor cortex while the non-pianist controls indicated left-larger-than-right asymmetry (Amunts et al, 1997 ). Houdayer et al ( 2016 ) identified balanced interhemispheric interactions along with improved piano skill proficiency. Specifically, ipsilateral silent period (ISP), a measure of callosal transmission, was asymmetric at the baseline, with the left hemisphere characterized by longer duration than the right hemisphere.…”
Section: Neural Adaptations Associated With Piano Learningmentioning
confidence: 99%